Anaerobic threshold determination in cycle ergometer from rating of perceived exertion - Santos, G. A. D.; Numata-Filho, E. S.; Rosa, T. D. S.; Passos Neves, R. V.; Simões, H. G.; Moreira, S. R. (The Journal of Strength and Conditioning Research, 2022)
The objective of the study was to investigate the validity of the rating of perceived exertion threshold (TRPE) for anaerobic threshold (AT) estimation during an incremental test (IT) on a cycle ergometer. Nineteen physically active and healthy men performed an IT on a cycle ergometer. The intensity corresponding to the AT was considered as the point immediately before the abrupt increase in blood lactate concentration ([La]) in the IT. TRPE was determined in the last intensity corresponding to perceptual response previous the 15 arbitrary units (AU) in the 15-point RPE scale. The heart rate (HR), [La], and RPE were obtained at the end of each stage of the IT. There was no significant difference between workload obtained from the AT (150 [120-150] watts) and TRPE (150 [120-150] watts) (p > 0.05). In addition, there were no differences between HR (AT, 139.5 ± 12.7 b·min-1 vs. TRPE, 141.9 ± 14.6 b·min-1, p > 0.05) and [La] (AT, 3.1 [2.8-3.2] mM vs. TRPE, 3.1 [2.9-3.7] mM, p > 0.05). There was a strong correlation between the intensities in AT and TRPE during the IT (r = 0.88). A substantial reliability (intraclass correlation coefficient = 0.84 [0.64-0.94 confidence interval 95%]) was evidenced, as well as a substantial agreement between the AT and TRPE intensities (Pc = 0.84), as confirmed by the Bland-Altman plot (-4.7 [-34.2/24.7]). TRPE was a predictor of the AT (ß = 1.146, R = 0.770, SEE = 15.070, p < 0.01). It can be concluded that TRPE is valid for AT estimation during an IT on a cycle ergometer.